Negentropic stabilization of metastable β-Ti in bulk metallic glass composites. (December 2016) - Zhang, L.; Zhang, H.F.; Li, W.Q.; Gemming, T.; Zhu, Z.W.; Fu, H.M.; Eckert, J.; Pauly, S.
Abstract: In order to obtain metastable β-type bulk metallic glass composites (BMGCs), understanding the thermodynamic stability of the β phase is crucial. The interface between β-Ti and the supercooled liquid in BMGCs is revealed to play an important role on stabilizing metastable β-Ti during solidification. Additional interfacial energy hampers the formation of α-Ti laths at the interface, and the critical cooling rate required to suppress the transformation from β-Ti to α-Ti in BMGCs is reduced. The result implies that metastable β-Ti in BMGCs is prone to precipitate ω-Ti rather than α-Ti, which is significant on understanding the microstructures of β-type BMGCs. Graphical abstract: